Letter from Henry A. Greer to James Curtis Booth, January 22, 1859 - Greer, Henry A. (1859)
James Curtis Booth (1810-1888) is elected a Professor of the Pennsylvania Horticultural Society for the year 1859.
Keywords: Booth, James Curtis, 1810-1888; Pennsylvania Horticultural Society; Chemistry teachers